Aspartate Transcarbamoylase from Escherichia coli: Electron Density at 5.5 Å Resolution - Warren, Stephen G. (1973)
The allosteric enzyme, aspartate transcarbamoylase (EC 2.1.3.2), has previously been shown in our x-ray diffraction studies to have D(3)-32 symmetry. There are six catalytic (C) and six regulatory (R) chains in the molecular complex (R(6)C(6)). Our three-dimensional x-ray diffraction study of this enzyme (R32, a = 131 Å, c = 200 Å) at 5.5 Å resolution shows a spatial arrangement of the two catalytic trimers C(3) above and below an equatorial belt of three regulatory dimers R(2). The molecule is about 110 × 110 × 90 Å in largest dimensions, and is shown here to contain a large central aqueous cavity about 50 × 50 × 25 Å in size. Location of the single sulfhydryl of each catalytic chain, and correlation of its reactivity with enzymatic activity in the molecule, suggests that the nearby active sites are most probably accessible from the central cavity, but probably not directly from the external solution. The most obvious access to the central cavity consists of six channels, each about 15 Å in diameter, near the regulatory region. A component of the regulatory mechanism may be modulation of access of substrates through these channels.